Using a bedside ultrasound (US), an emerging technology, to confirm endotracheal tube (ETT) location in adults in emergency department - Bom, Rabin; Maharjan, Ramesh Kumar; Neupane, Ram Prasad (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Airway management is the most important aspect of patient treatment in emergency medicine. Prompt confirmation of Endotracheal Tube (ETT) in larynx is imperative for avoiding complications in sick patient. With quick learning graph, Point of Care Ultrasound (POCUS) has high sensitivity and specificity for detection of ETT in place.Method: A prospective observational study was conducted at adult Emergency Department of Tribhuvan University Teaching Hospital among patients undergoing intubation for various reasons. Transtracheal POCUS was used to confirm the tube placement. Time to confirm tube by POCUS in trachea and by bilateral chest auscultation was noted.Result: Of the 71 intubations, 68 were correctly identified to be in trachea and 3 in esophagus, resulting in sensitivity and specificity of 100% each. Transtracheal POCUS was the fastest method to determine endotracheal intubation (8.08 ± 1.69 seconds) compared to bilateral chest auscultation (22.37 ± 3.45 seconds).Conclusion: With high sensitivity and NPV for confirmation of correct endotracheal tube intubation and early detection, transtracheal POCUS in emergency could be a useful tool for prompt localization of ETT and instant action needed before final confirmation by other means.